NH3-promoted heterogeneous reaction of SO2 to sulfate on α-Fe2O3 particles with coexistence of NO2 under different relative humidities. (1st October 2021) - He, Xiang; Wu, Jian-Jun; Ma, Zhi-Cheng; Xi, Xi; Zhang, Yun-Hong
Abstract: Heterogeneous reactions play an essential role in the research area of formation processes of secondary aerosols. In this study, heterogeneous reactions of NH3 /SO2 /NO2 with α-Fe2 O3 particles at different relative humidities (RHs) were investigated by using a gas-flow system combined with diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The results show that the presence of NH3 leads to the rapid conversion of SO2 to sulfate as a result of the proton transfer function and neutralization on the α-Fe2 O3 particles in dry condition. NH3 can also promote the hydrolysis of NO2 dimers to HONO formation and result in the formation of more sulfate on the particle surface in humid conditions. On the other hand, water vapor plays both positive and negative roles in the uptake of SO2 during the reaction processes. When the RH increases from 0% to 62%, the formation rate of sulfate and uptake coefficient for SO2 in the initial stage increase about 3-fold. However, due to the inhibition effect of water layer between trace gases and active surface, the above values of reaction kinetic decrease about 21% when the RH increases from 62% to 72%. Our results may provide insight into the effects of NH3 and RH for the converting SO2 into sulfate on α-Fe2 O3 particles, which supply basic data for the formation of secondary particles in field studies of atmospheric environment. Graphical abstract: Image 1 Highlights: Combined effects of NH3 /SO2 /NO2 and RH on secondary sulfate formation were studied. The promotion mechanisms of NH3 at dry and humid conditions were proposed. Increasing RHs play both positive and negative roles in the uptake of SO2 . The acidity of the α-Fe2 O3 particles increases at humid condition.